ANALISIS DETERMINAN PENGELUARAN KONSUMSI AKHIR RUMAH TANGGA DI INDONESIA: MODEL LSDV DAN ARDL - Kusuma, Natasya Ayu; Laut, Lorentino Togar (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 6 No 2 (2021): Jurnal Kajian Ekonomi dan Kebijakan Publik, 2021)
The Indonesian economy from 2010-2020 continued to experience a slowdown. One of them is, if viewed from the demand side, household final consumption expenditures are the cause of the economic slowdown both at the regional and national levels. This study aims to: 1) Know the provincial dummy that has a significant difference from one province to another with the reference province is DKI Jakarta, 2) The influence of macroeconomic variables such as GDP, inflation, PMA, Government Consumption Expenditure and Oil and Gas Imports on Final Consumption Expenditures Households, 3) variables that have an impact on the short term and long term on household final consumption expenditure in Indonesia. This study uses 2 methods with different objectives, 1) to analyze the differences between provinces using the LSDV (Least Square Dummy Variable) Panel Regression approach using the Provincial dummy and DKI Jakarta benchmarks with a time period of 2015-2020 and the variables used are GRDP, inflation, Government consumption expenditures and the GER ratio of women/ men in tertiary institutions. The results obtained are that there is a significant difference between West Papua and DKI Jakarta with the dummy coefficient for West Papua -0.2085, so that there is a gap between West Papua and DKI Jakarta. 2) by using the ARDL method, there are two variables that are affected in the short and long term, namely the GDP and FDI variables with each variable having a significant negative effect on household final consumption expenditure in Indonesia for the 2010-2020 period.